Hand rehabilitation based on the RobHand exoskeleton in stroke patients: A case series study - Barria, Patricio; Riquelme, Matías; Reppich, Hannah; Cisnal, Ana; Fraile, Juan-Carlos; Pérez-Turiel, Javier; Sierra, David; Aguilar, Rolando; Andrade, Asterio; Nuñez-Espinosa, Cristian (Frontiers in Robotics and AI, 2023)
The RobHand (Robot for Hand Rehabilitation) is a robotic neuromotor rehabilitation exoskeleton that assists in performing flexion and extension movements of the fingers. The case study assesses changes in manual function and hand muscle strength of four selected stroke patients after completion of an established training program. In addition, safety and user satisfaction are also evaluated. The training program consisted of 16 sessions; two 60-minute training sessions per week for eight consecutive weeks. During each session, patients moved through six consecutive rehabilitation stages using the RobHand. Manual function assessments were applied before and after the training program and safety tests were carried out after each session. A user evaluation questionnaire was filled out after each patient completed the program. After evaluating the collected data it was concluded that the RobHand is a safe assistive technology and users were satisfied with the system. This was supported by the absence of significant adverse events such as skin lesions or fatigue and an average score of 4 out of 5 on the Quebec User Evaluation of Satisfaction with Assistive Technology 2.0 Scale. Users were most satisfied with the weight, comfort, and quality of professional services. However, there were no significant changes in the manual function tests after the training program. This could be due to the high influence of the stroke stage on motor recovery since tests were performed with chronic patients. Hence, future studies should evaluate the rehabilitation effectiveness of the repetitive use of the RobHand exoskeleton on subacute patients. The trial has been registered in ClinicalTrials.gov with the number NCT05598892.